%%P\left({\overline E}_1\right);\;P\left({\overline E}_2\right)%%

%%P\left({\overline E}_1\right)%%

Berechne das Gegenereignis zu %%P\left(E_1\right)%%.

%%P\left({\overline E}_1\right)+P\left(E_1\right)=1%%

%%\left|{}-P\left(E_1\right)\right.%%

%%P\left({\overline E}_1\right)=1-P\left(E_1\right)%%

Für %%P\left(E_1\right)%% 0,4 einsetzen.

%%\Rightarrow P\left({\overline E}_1\right)=1-0{,}4=0{,}6%%

%%P\left({\overline E}_2\right)%%

Berechne das Gegenereignis zu %%P\left(E_2\right)%%.

%%P\left({\overline E}_2\right)+P\left(E_2\right)=1%%

%%\left|{}-P\left(E_2\right)\right.%%

%%P\left({\overline E}_2\right)=1-P\left(E_2\right)%%

Für %%P\left(E_2\right)%% den Wert 0,7 einsetzen.

%%\Rightarrow P\left({\overline E}_2\right)=1-0{,}7=0{,}3%%